2019
DOI: 10.2298/abs181020028c
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the phylogeography of the nose-horned viper (Vipera ammodytes, Linnaeus, 1758) in the Central Balkan Peninsula

Abstract: Seven genetic clades have been recognized within the species Vipera ammodytes (nose-horned viper); however, the precise phylogenetic position of many Balkan populations is unknown. We used Bayesian analysis of the mtDNA sequences from the 16S rRNA mtDNA gene obtained from 47 individuals (26 novel samples sequenced in this study and 21 sequences available from GenBank). Our results show that sampled nose-horned vipers from localities in Serbia are clustered within three clades: the northeastern (23 individuals)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Τhe mitochondrial gene‐tree and the mptp analyses revealed 11 strongly supported mitoclades (Figure 4a and Figure S4). Ten of them had been reported before (Čubrić et al, 2019; Ursenbacher et al, 2008) and are confirmed here with more sampling localities that increase their known geographical distribution (Figure 4b). An eleventh one is reported for the first time from the North‐Eastern Peloponnese (NEP), as sister to the mitoclade distributed in the southeast Balkan mainland (South 1 + 2).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Τhe mitochondrial gene‐tree and the mptp analyses revealed 11 strongly supported mitoclades (Figure 4a and Figure S4). Ten of them had been reported before (Čubrić et al, 2019; Ursenbacher et al, 2008) and are confirmed here with more sampling localities that increase their known geographical distribution (Figure 4b). An eleventh one is reported for the first time from the North‐Eastern Peloponnese (NEP), as sister to the mitoclade distributed in the southeast Balkan mainland (South 1 + 2).…”
Section: Resultssupporting
confidence: 89%
“…A black dashed line shows the approximate geographical separation between the North Balkan Clade (NBC) and the South Balkan Clade (SBC). Dashed grey lines show the distribution area of the respective mitochondrial clade, according to previous knowledge (Čubrić et al, 2019; Ursenbacher et al, 2008). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Balkan Peninsula was one of the important glacial refugia for European biodiversity and one of the sources for the recolonization of the continent after Pleistocene glaciations (Guillaume et al 1997, Džukić & Kalezić 2004, Böhme et al 2007. Accordingly, Serbian batracho-and herpetofauna is characterized by: (1) relatively high taxonomical, morphological and genetic diversity (Crnobrnja-Isailović 2007, Ursenbacher et al 2008, Gvoždík et al 2010, Vukov et al 2013, Wielstra et al 2013b, Čubrić et al 2019, Stratakis et al 2022, (2) ancestral phylogeographic clades, relict populations and microrefugia (Džukić & Pasuljević 1979, Džukić & Purger 1988, Sotiropoulos et al 2007, Arntzen et al 2007, Hofman et al 2007, Ljubisavljević et al 2010), (3) peripheral populations and marginal species' ranges (Džukić & Kalezić 2004, Vukov et al 2013) and (4) hybridization and hybrid zones (Gvoždík et al 2010, Stöck et al 2012, Arntzen et al 2014, Dufresnes et al 2015, Jablonski et al 2016, Urošević et al 2020.…”
Section: Introductionmentioning
confidence: 99%